2022
DOI: 10.1039/d2cb00010e
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal autoinhibitory module of the A1 domain in von Willebrand factor stabilizes the mechanosensor catch bond

Abstract: The N-AIM of VWF-A1 forms a Rotini-like structure, therefore partially autoinhibit VWF-A1–GPIbα interaction. The N-AIM acts as a defending sword to protect and stabilize the VWF-A1 structure under harsh environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…( 2008 ); Zhao et al. ( 2022 )) and its effect on long-term ( s) dynamics of adherent platelets in shear remain out of the scope of the present study and should be addressed in future. Finally, in present work we use a parallel-plane geometry of the system, similar to a typical microfluidic flow chambers or lab-on-a-chip devices for laboratory studies of platelet hemostasis (Six et al.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…( 2008 ); Zhao et al. ( 2022 )) and its effect on long-term ( s) dynamics of adherent platelets in shear remain out of the scope of the present study and should be addressed in future. Finally, in present work we use a parallel-plane geometry of the system, similar to a typical microfluidic flow chambers or lab-on-a-chip devices for laboratory studies of platelet hemostasis (Six et al.…”
Section: Discussionmentioning
confidence: 94%
“…( 2021 ); Zhao et al. ( 2022 )). The typical tension force required for activation of VWF monomers was estimated as 20–35 pN by Fu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the conventional BFP, advancements in the setup have led to the development of both a dual BFP and fluorescent BFP setup. The BFP-DFS applications include but are not limited to ligand binding kinetics [14][15][16][17][18][19] , cytoskeleton mediated receptor activation [20][21][22][23][24] , 2D receptor conformational changes 25,26 and dual receptor crosstalk 27,28 . More broadly, the elucidation of these mechanisms has contributed significantly to research in the fields of cancer biology, thrombosis, and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the structural insights underlying A1-GPIba interaction dynamics is significant towards developing novel anti-thrombotic therapeutics. 10,46,47 Nevertheless, how N-AIM or Lp interacts with A1-GPIba in trans and affects catch bond behaviors remains elusive. To this end, the present study aims to employ a series of computational biology platforms to predict soluble Lp conformation and to define its role in regulating A1-GPIba catch bond.…”
Section: Introductionmentioning
confidence: 99%
“…By combining the biomembrane force probe (BFP), MD simulation and microfluidic perfusion assays, our recent study demonstrated that N-AIM stabilizes A1 catch bond behavior and serves as a mechano-regulator of VWF activity in cis . 46 10 Clinically, the FDA has recently approved Anti-VWF Caplacizumab (ALX-0081) to treat thrombotic thrombocytopenic purpura (TTP) with less bleeding side effects. 26 Its epitope has subsequently mapped to the N-AIM sequence of VWF A1 domain.…”
Section: Introductionmentioning
confidence: 99%